2017
DOI: 10.1115/1.4036020
|View full text |Cite
|
Sign up to set email alerts
|

Seepage Monitoring of an Embankment Dam Based on Hydro-Thermal Coupled Analysis

Abstract: Distributed temperature sensing (DTS)-based fiber optic sensors are widely used for monitoring spatially continuous temperature distribution in structures. In this research, hydro-thermal (H-T) coupled analysis is used to monitor seepage conditions in an embankment dam. Variably saturated two-dimensional heat transport (VS2DHI), a computer code developed by the U.S. Geological Survey, was used for this coupled analysis. From the coupled analysis, the temperature profile for a dam with an artificially generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…According to the results in Table 4, the average RMSE, R 2 , and Re values for the Ren model, Lu model, and Côté and Konrad model were 0.86°C, 0.95, and 3.57%, respectively, and each evaluation index reflected a satisfactory result. e Lu model is a thermal conductivity model that has been widely used in recent years [43,44] and provides a good simulation effect [18]. Research by Ren et al [18] revealed that coupled hydrothermal modeling based on the Lu model yielded better results than the traditional modeling technique, suggesting that changes in the equivalent thermal conductivity model can promote the accuracy of coupled riparian zone modeling.…”
Section: Evaluation Of the Simulation Results Of Different Equivalent Ermal Conductivity Modelsmentioning
confidence: 99%
“…According to the results in Table 4, the average RMSE, R 2 , and Re values for the Ren model, Lu model, and Côté and Konrad model were 0.86°C, 0.95, and 3.57%, respectively, and each evaluation index reflected a satisfactory result. e Lu model is a thermal conductivity model that has been widely used in recent years [43,44] and provides a good simulation effect [18]. Research by Ren et al [18] revealed that coupled hydrothermal modeling based on the Lu model yielded better results than the traditional modeling technique, suggesting that changes in the equivalent thermal conductivity model can promote the accuracy of coupled riparian zone modeling.…”
Section: Evaluation Of the Simulation Results Of Different Equivalent Ermal Conductivity Modelsmentioning
confidence: 99%
“…Referring to the customary engineering design data and literature, the influencing parameters to account for the seepage and temperature fields are given in Table 1. Among these parameters, the unsaturated seepage parameters are selected from [1,4,30], and the other parameters are based on empirical evaluations and engineering design data [31]. The thermal diffusion coefficient is 0.01 m, and the thermal conductivity of air and water are, respectively, considered to be 0.024 W/(m⋅ ∘ C) and 0.58 W/(m⋅ ∘ C).…”
Section: Model Parametersmentioning
confidence: 99%
“…In normal operating conditions, the temperature of dam foundation and dam body are mainly affected by the seepage conditions. Water movement in the rock-soil medium of the dam can affect its temperature distribution during the time [1]. Consequently, studying the coupled temperature and seepage effects of the embankment dam may provide a theoretical basis to make a correlation between seepage and temperature fields, in order to find the safe states of the seepage [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prototype monitoring is an important part of safety evaluation for rockfill dams [11][12][13][14][15]. In general, pore pressures, earth pressures, seepage pressures, seepage discharge, and displacement are measured during construction and the initial impoundment.…”
Section: Introductionmentioning
confidence: 99%